2023
DOI: 10.1021/acs.jafc.3c00283
|View full text |Cite
|
Sign up to set email alerts
|

Shikimic Acid Regulates the NF-κB/MAPK Signaling Pathway and Gut Microbiota to Ameliorate DSS-Induced Ulcerative Colitis

Abstract: Shikimic acid (SA) is a compound extracted from the plant anise and has anti-inflammatory effects. However, any impact on intestinal inflammation or mechanisms involved has not been investigated. The present study used a dextran sulfate sodium (DSS)-induced mouse colitis model to investigate the effects of SA on intestinal inflammation. Intragastric administration of SA slowed DSS-induced weight loss, reduced disease activity index (DAI) score, enhanced the intestinal barrier, reduced the destruction of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To further investigate the mechanism of action by which WBP relieves colonic inflammation, we investigated the involvement of the NF-κB and MAPK signaling pathways to inflammation regulation. NF-κB functions as a transcription factor that forms a heterodimer with the p65/p50 subunit and inhibitory protein IκB within the cytoplasm [51]. Upon activation of the signaling pathway, the degradation of IκB proteins enables the translocation of NF-κB dimers into the nucleus, thereby regulating the expression of target genes [52].…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the mechanism of action by which WBP relieves colonic inflammation, we investigated the involvement of the NF-κB and MAPK signaling pathways to inflammation regulation. NF-κB functions as a transcription factor that forms a heterodimer with the p65/p50 subunit and inhibitory protein IκB within the cytoplasm [51]. Upon activation of the signaling pathway, the degradation of IκB proteins enables the translocation of NF-κB dimers into the nucleus, thereby regulating the expression of target genes [52].…”
Section: Discussionmentioning
confidence: 99%
“…Pine needles contain essential oils, terpenes, and polyphenols, which promote the absorption and utilization of nutrients in the digestive tract, and the unique aroma of pine needles improves the flavour of the feed and enhances appetite [ 20 ]. Previous studies have reported that proanthocyanidin and shikimic acid in pine needles can control and regulate the expression of cellular pro-inflammatory factors and improve the body's immune response [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…When it accumulates to sufficiently high levels, it impairs, restricts, or even kills immune cells [70]. Additionally, shikimic acid demonstrated anti-inflammatory effects [71], and homogentisic acid confers a survival advantage during host infection in Bordetella parapertussis [72].…”
Section: Discussionmentioning
confidence: 99%